2022
DOI: 10.3171/2021.12.focus21603
|View full text |Cite
|
Sign up to set email alerts
|

Unaccounted for enteral volume loss linked to delayed cerebral ischemia after subarachnoid hemorrhage

Abstract: OBJECTIVE Delayed ischemic neurological deficit (DIND) is seen as a clinical manifestation of cerebral vasospasm and is a significant cause of morbidity and mortality following aneurysmal subarachnoid hemorrhage (aSAH). Currently, the standard of care for DIND prevention in patients who have sustained aSAH is prophylactic nimodipine therapy and ensuring adequate fluid intake, alongside other treatments such as bowel care. Osmotic laxatives trap water within the bowel lumen to accelerate the transport of the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…In patients with aSAH, maintaining euvolemia can be beneficial in preventing DCI and improving functional outcomes. 320,321 2b B-NR 3. In patients with aSAH and symptomatic vasospasm, elevating systolic BP values may be reasonable to reduce the progression and severity of DCI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with aSAH, maintaining euvolemia can be beneficial in preventing DCI and improving functional outcomes. 320,321 2b B-NR 3. In patients with aSAH and symptomatic vasospasm, elevating systolic BP values may be reasonable to reduce the progression and severity of DCI.…”
mentioning
confidence: 99%
“…Maintenance of euvolemia can be effective to prevent DCI and improve functional outcomes after SAH. 356 Gelder and colleagues 321 found that 58% of patients with documented volume depletion developed DCI. Hypervolemia is associated with worse outcomes and higher rates of complications (see Section 8).…”
mentioning
confidence: 99%
“…In support of this, in 1 study, including 105 patients with aSAH, investigators found that among patients who developed diarrhea, all of whom had received osmotic laxatives, 58% of patients developed delayed ischemic neurological deficits, compared with 8.6% of patients without diarrhea (odds ratio, 15.30 [95% CI, 3.92-59.14]; P=0.0001). 2 (1) Avoid prophylactic hemodynamic augmentation Consistent with previous guidelines, the 2023 AHA/ ASA aSAH guidelines recommend against the induction of hypervolemia and hypertension to prevent vasospasm and DCI. The guidelines state that induction of hypervolemia is potentially harmful because of the association with excess morbidity (class of recommendation (COR) 3: harm [strong], level of evidence B: randomized) and that prophylactic hemodynamic augmentation should not be performed to reduce iatrogenic patient harm (COR 3: harm [strong], level of evidence B: randomized).…”
Section: Recommendations and Evidencementioning
confidence: 96%
“…DCI occurs in ≈30% of patients with aSAH and it is one of the leading causes of functional deficits and mortality after aSAH. [1][2][3][4][5][6][7][8][9] Hypovolemia and intravascular depletion are thought to be risk factors for the development of symptomatic vasospasm and DCI. In support of this, in 1 study, including 105 patients with aSAH, investigators found that among patients who developed diarrhea, all of whom had received osmotic laxatives, 58% of patients developed delayed ischemic neurological deficits, compared with 8.6% of patients without diarrhea (odds ratio, 15.30 [95% CI, 3.92-59.14]; P=0.0001).…”
Section: Recommendations and Evidencementioning
confidence: 99%
See 1 more Smart Citation